Implicit Discrimination in Hiring - Real World Evidence - Dan-Olof Rooth (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2007)
This is the first study providing evidence of a new form of discrimination, implicit discrimination, acting in real economic life. In a two-stage field experiment we first measure the difference in callbacks for interview for applicants with Arab/Muslim sounding names compared to applicants with Swedish sounding names using the correspondence testing methodology. In the second stage of the experiment we measure, for a sample of the recruiters involved, their explicit and implicit attitudes/performance stereotypes by the means of explicit questions and the implicit association test (IAT). We find (i) only weak correlations between explicit attitudes/performance stereotypes and implicit performance stereotypes but (ii) a strong and statistically significant negative correlation between the implicit performance stereotypes and the callback rate for an interview for applicants with Arab/Muslim sounding names, but not for applicants with Swedish sounding names. These results indicate that implicit discrimination acts differently compared to explicit discrimination and that it is an important determinant of the hiring process.
Keywords: 330